The Islamic Basis of Vocational Education - AbdulAziz A.AI-mohaimeed (Journal of Islamic Studies, 2003)
This is a study aimed at describing and analyzing what the resources of Islamic education include about vocational education, especially the Quranic verses and the sayings of the Prophet, peace be upon him, in addition to the explanations of these verses and sayings which had been written by some Muslim scholars in the past. In accordance with the main objective of this study, which is tracing the Islamic bases of vocational education, some concepts, principles, values and facts have been discussed, such as the Islamic interpretation of human behavior and work, worship and work in building and maintaining life, and the relation between human abilities ,talents and natural recourses of energy. Thirteen main Islamic bases of vocational education have been derived from the Islamic education literature pertaining to this subject. Finally, some recommendations were made in the light of the study with the purpose of building vocational education policies, goals curricula, and practices on the Islamic basis and concepts of this field of education, and further studies were suggested.